Development level of Physical Education students’ moral judgement of Santa Maria Federal University / RS - Gustavo Roese Sanfelice; Mauro Myskiw (Journal of Physical Education (Maringá), 2008)
The present study has the aim to analyze the moral judgement development level of students from 1st to 7th semesters of Physical Education Course of UFSMS based on Laurence Kohlberg’s theory (1958). The search is a survey type. Students answered a question schedule (Sociomoral Reflection Objective Measure – S.R.O.M.) with 16 closed questions, with two moral dilemmas. The analysis of data was performed using descriptive and inferential statistics. Among academics from 1st semester, 44,44% were in the third stage and 52,6% in the forth stage. Considering the significance level as p > 0,05, we verify there isn’t significant difference among the groups and that all people are in the conventional level of Kohlberg’s moral judgement belonging to the same group, suggesting there is no difference in the cognitive reasoning related to moral between 1st and 7th semester.